A note on forecasting the rate of change of the price of oil: Asymmetric loss and forecast rationality - Christian Pierdzioch; Jan-Christoph Rülke (Economies, 2013)
We study whether forecasts of the rate of change of the price of oil are rational. To this end, we consider a model that allows the shape of forecasters' loss function to be studied. The shape of forecasters' loss function may be consistent with a symmetric or an asymmetric loss function. We find that an asymmetric loss function often (but not always) makes forecasts look rational, and we also report that forecast rationality may have changed over time.
Keywords: 330; oil price; forecasting; loss function; rationality of forecasts